The Rationale for Behaviour Patterns of Violence Against Women by Their Intimate Partners - Costa, King; Shai, Violet (My University, 2020)
The problem of Gender Based Violence and the complexity of its multi-perspectival and multi-layered description within social sciences has become a major concern in South Africa and the world at large. Organisations such as the United Nations Educational Scientific and Cultural Organisation (UNESCO) and the World Health Organisation (WHO) are amongst many global leading advocacy voices against gender based violence, especially intimate partner violence. This study was focused on the rationale for behavioural patterns of intimate partner violence and intimate partner homicide. The units of analysis of this study involved male perpetrators who were incarcerated across four maximum correctional centres in the Gauteng Province of South Africa. A total of 12 inmates were selected purposively as interview participants in the study. The ontological position of this study was within interpretivist tradition with phenomenological epistemological approach. Interpretive methods of enquiry are located within the broad qualitative research methods, which was the foundation to this particular investigation. The semi structured questionnaires were constructed along the philosophical and scientific prescripts of philosophical research. Findings established that the rationale for intimate partner violence and intimate partner femicide are the anger, lack of communication, social constructs and toxic behaviour as the causes of violence in intimate relationships. This was reflected by participants as the contributing factor to their violent behaviour. Theories of intimate partner violence also explain most of the behaviour related patterns are associated with the stress. Cultural norms and societal expectations were found to influence the behaviour pattern of perpetrators. The economical exclusion subsequent to the Beijing Conference on women empowerment and freedom, as well as social exchange theory further suggest the pressures on male perpetrators and their roles as expected by culture and society are the causes of frustration and anger which end up in violent behaviour and femicide.
Keywords: Intimate partner femicide; Intimate partner violence; Intimate partner homicide; gender based violence